KONFLIK LAHAN PERKEBUNAN SAWIT DI DESA MUKTI UTAMA KEC.LONG MESANGAT KABUPATEN KUTAI TIMUR. - Zainal Mustajab (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTThe purpose of writing this essay is to find out Peemasalahan between villagers Mukti Utama with PT.GSA (Gemilang Sejahtera Abadi) related to the cultivation of land hereinafter referred to as conflict / dispute in the opening or cultivation of plantation land and to know setatus land of the villagers of Mukti Utama Village.In the opening of the land, the residents demanded because the land is cultivated by PT.GSA (Gemilang Sejahtera Abadi) the land is owned by a legal person proven by important documents in the form of Land Status Certificate (SKKT) issued by Stakeholders / Customary Institutions in this case the Chief Customary Desa Mukti Utama.dan residents requested that the company recognize the existence of the land in accordance with Law No.32 on environmental protection and maintenance.Regarding the rules on land clearing, especially in the field of plantation has been regulated by Regulation of Minister of Agrarian No.2 About location permit and Regulation of Minister of Plantation No.140 Year 2007 concerning plantation permit, even in the rule have been explained if in land clearing or cultivation of company land it is mandatory to re-examine the permit to be socialized to the local community to synchronize the location permit permits granted by the government in this case the Government of East Kutai Regency in particular, In this case the company PT.GSA (Gemilang Sejahtera Abadi) which aims to prevent the occurrence conflicts / land disputes with local residents, but what happens on the part of the company does not heed the rules so that after the clearing of land there is overlapping of land and citizens demanded to the company and from the company promised to solve the problem of conflict / disput eta land that occurred with the villagers Mukti Utama.